The Soul of the Earth and the Value of Art. Joan Miró, Rodolf Llorens, Antoni Tàpies, Eduard Nicol... - Cuscó-Clarasó, Joan (Journal of Catalan Intellectual History, 2011)
This paper puts side by side philosophy and artistic creation in Catalonia in the twentieth century. We have to grasp how art and philosophy are able to generate and share thought and expression: a vision and a unique understanding of reality. This is a key reflection to understanding our times and reflects on the meaning and value of art and philosophy, humanism and the human condition in a society doomed to noise, to urgencies, and to lack of dialogue. key words Art, creation, Eduard Nicol, Antoni Tàpies, Catalan philosophy, Joan Miró, Josep Soler, Rodolf Llorens.